Abschätzung der Vorlastabhängigkeit in der Intensivmedizin – Schritt für Schritt - Adler, Christoph; Treskatsch, Sascha; Pfister, Roman; Michels, Guido (DMW - Deutsche Medizinische Wochenschrift, 2019)
The determination of the cardiac preload is still a challenge for intensive care physicians. In addition to clinical assessment, both non-invasive and invasive methods exist for evaluating fluid responsiveness. The following article demonstrates one possible approach for systematic assessment of fluid responsiveness using a practical algorithm for critical care patients.
Keywords: Volumen; Intensivmedizin; Hämodynamik; Ultraschall; Echokardiografie